Correlation of Clinical Severity and Laboratory Parameters with Various Serotypes in Dengue Virus: A Hospital-Based Study - Pooja Rao; Achappa Basavaprabhu; Suchitra Shenoy; Nikhil Victor Dsouza; Basavaiah Sridevi Hanaganahalli; Vaman Kulkarni (International Journal of Microbiology)
Objectives. Dengue fever, being hyperendemic with analogous presentations as in many other acute febrile illnesses, poses a challenge in diagnosis during the acute stage. Additionally, the coexistence of multiple serotypes further complicates the disease prognosis. The study was undertaken to determine the dengue virus serotypes, clinical, and laboratory markers as predictors in the severity of infection. Methods. A prospective study was conducted among 106 patients admitted with acute febrile illness having positive NS1 antigen/IgM ELISA. Clinical data were extracted from medical records including demographics, presence of comorbid conditions, clinical presentation, laboratory investigations, and course including length of hospital stay and outcome. Detection of dengue serotypes was done by multiplex reverse transcriptase polymerase chain reaction (RT_PCR). Results. Out of 106 RT-PCR-confirmed cases, DENV-3 was the most common serotype found in 56 (52.8%) patients, followed by DENV-3 and DENV-4 coinfection in 27 (25.4%) patients. Coinfection with more than one serotype was witnessed in our study. Raised liver enzymes and increased ferritin are good biomarkers in differentiating dengue from severe dengue with cutoff levels for AST (134 U/L), ALT (88 U/L), and ferritin (3670 ng/ml). Musculoskeletal, followed by gastrointestinal, manifestations were comparatively higher than respiratory and cutaneous manifestations. Conclusion. This study provides more information on the dengue serotypes. The clinical spectrum along with laboratory parameters such as ferritin, liver enzymes, platelet can be used as potential biomarkers in prediction of dengue severity. The data demonstrated will be useful in early detection and monitoring of the disease.